DIABETES MELLITUS LIFESTYLE MANAGEMENT AS AN EFFORTS TO IMPROVE QUALITY OF LIFE FOR DIABETES MELLITUS PATIENTS - Riska Rohmawati; Lono Wijayanti; Rahayu Anggraini; Ratna Yunita Sari; Imamatul Faizah; Dany Irawan (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Complications experienced by DM patients will affect the patient's quality of life. Efforts that can be done to maintain the quality of life, one of which is by lifestyle management. This training is expected to increase the knowledge and skills of health cadres in teaching lifestyle management to improve the quality of life of people with diabetes mellitus. The method used in this community service activity is to provide health counseling. This activity was carried out for one month and was attended by 15 cadres and 50 people with DM. Quality of life is measured by DQOL (Diabetes Quality of Life). After one month of service, it was found that 98% of the quality of life of people with DM increased (good). Lifestyle management can maintain the quality of life of people with DM through maintaining stable blood sugar levels